Occupational accidents with sharp devices among dental undergraduate students - Maria Helena Monteiro de Barros Miotto; Raquel Morais Rocha (Universidade de Fortaleza, 2012)
Objective: To evaluate the prevalence of accidents among the students of Dentistry College in Federal University of Espírito Santo, Brazil, in the first academic semester of 2010. Methods:This is an observational cross-sectional analytical study, with a random sample comprising 159 students, given the opportunity to respond to a self-administered questionnaire, with 28 questions about biosafety, occupational accidents and vaccination. Results: Among 153students who filled the questionnaire, 42 students (27,5%) asserted having suffered some kind of accident. Proportion of accidents among students attending from first to fifth academic semester was 5,1% (n=2), reaching 50,7% (38 students) among the ones attending from sixth to ninth semester (p=0,000). Ten (23,8%) students reported not using individual protection equipment at the time of the accident. Only 4 (9.5%) students have registered their injury by the Occupational Accident Communication. Conclusion: The number of injured students is significant, mostly among the ones attending from sixth to ninth semester, and accidents involving needlestick or cut with sharp devices were the most prevalent.